THU0647 Longitudinal study of long-term poverty and persistent depressive symptoms in sle. (12th June 2018) - Yelin, E.; Yazdany, J.; Trupin, L.; McCormick, N.; Katz, P.
Abstract : Background: A prior study found that persons with SLE in long-term poverty have greater accumulation of disease damage over 6 years than those exiting poverty or never in poverty 1 . The present study evaluates the effect of long-term poverty status on depressive symptoms over the same duration of time. Objectives: Analyse the impact of long-term poverty on prevalent and incident persistent depression after accounting for other risk factors for depression among persons with SLE. Methods: Data are from the UCSF Lupus Outcomes Study in which persons with SLE were recruited in 2003 throughout the U.S. and interviewed annually through 2015. In each year we characterised respondents' poverty status based on household income and family size and administered the CESD measure of depressive symptoms, defining a high level of depressive symptoms using a validated SLE-specific cutpoint (≥24) associated with a formal diagnosis of depression 2 . Prevalent persistent depression was defined as having high levels of depressive symptoms for ≥3 years between 2009 and 2015. Incident persistent depression used the same criteria, measured only among those who had low levels of depressive symptoms between 2006 and 2009. Logistic regression was used to estimate the impact of being poor in every year from 2003–2009, permanently leaving poverty by 2009, or never being poor on prevalent and incident persistent depression, with and without adjustment for gender, age, marital status, race/ethnicity, education, disease duration, extent of accumulated damage by 2009 using the Brief Index of Lupus Damage 3, smoking status, and BMI. Results: 535 persons with SLE were interviewed in each year from 2003 to 2015 (94% female, 65% non-Hispanic whites, mean age in 2003 50 years, range 20–83, mean disease duration 17 years, range 1–51). Between 2003 and 2009, 81% were never poor, 8% exited poverty, and 11% were poor in every year. 89 of the 535 (16.6%) met the study definition of prevalent persistent depression; 23 (7.4%) of the 312 free of high levels of depressive symptoms from 2006–2009 had incident persistent depression as of 2015. Table 1, below, indicates that those who were poor in every year had significantly higher rates of prevalent and incident persistent depression than those exiting poverty or never poor. Conclusions: Public policy to help persons with SLE stay out of poverty or to exit poverty may lower their rates of prevalent and incident persistent depression. Attention to the economic status of persons with SLE should be part of an overall treatment strategy including treatment for depression since such attention may help reduce accumulation of damage as well as reduce the prevalence and incidence of persistent depression. References: [1] Yelin E, et al. Arthritis rheumatol2017;69:1612–1622. [2] Julian L, et al. Arthritis care & research2011;63:884–890. [3] Yazdany J, et al. Arthritis care & research2011;63:1170–1177. Disclosure of Interest: E. Yelin Grant/research support from: Robert Wood Johnson Foundation Investigator in Health Policy Award, J. Yazdany: None declared, L. Trupin: None declared, N. McCormick: None declared, P. Katz: None declared